Why Do Leaders Express Humility and How Does This Matter: A Rational Choice Perspective - Yang, JianChun; Zhang, Wei; Chen, Xiao (Frontiers in Psychology, 2019)
The utility of leader humility expressing behavior has been examined by several studies across multiple levels. However, our knowledge about why leaders express humility continues to be sparse. Drawing on rational choice theory, this paper proposes a model examining whether followers’ capability triggers leader’s humility expressing behavior and how followers’ interpretations of it influence its effectiveness. Results from 278 leader-follower dyads from a time-lagged research design showed that followers' capability as perceived by the leader is positively related to leader-expressed humility and, in turn, this behavior would conditionally enhance follower-trust, that is, followers will trust the humble leader less when they attribute leader’s expressed humility more to be serving impression management motives. Several theoretical and practical implications of this observation are discussed in this study.